2014
DOI: 10.1039/c3ce42208a
|View full text |Cite
|
Sign up to set email alerts
|

Novel alkali and alkaline earth metal coordination polymers based on 1,4-naphthalenedicarboxylic acid: synthesis, structural characterization and properties

Abstract: Six new alkali and alkaline earth metal coordination polymers based on rigid 1,4-naphthalenedicarboxylic acid (H 2 NDA), [Li(HNDA) 5), and [Ba(NDA)(DMF)] ( 6) have been synthesized under solvothermal conditions in order to evaluate the coordination behavior of H 2 NDA towards Li + , Na + , Mg 2+ , Ca 2+ , Sr 2+ , and Ba 2+ ions and the structural features of the resulted polymeric complexes. Their structures were determined by single-crystal X-ray diffraction studies. The coordination number of the metal ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 80 publications
(3 reference statements)
2
19
0
Order By: Relevance
“…Sr(NDC) was readily synthesized in large quantities (see S3) and good agreement was obtained between the powder x-ray diffraction (PXRD) of the as-synthesized sample and the previously reported structure (see Figure 9 and S3 for experimental details). Extreme activation condi- tions were originally found to be necessary to overcome the strong binding between the DMF solvent and the open metal site and allow it to release through the narrow pore constrictions in the framework, 28 and we found that heating at 300 • C for 16 hours led to a structural change in the PXRD pattern of the activated sample. The primary reflection is preserved, suggesting that the unit cell remains unchanged.…”
Section: Experimental Activationmentioning
confidence: 71%
See 1 more Smart Citation
“…Sr(NDC) was readily synthesized in large quantities (see S3) and good agreement was obtained between the powder x-ray diffraction (PXRD) of the as-synthesized sample and the previously reported structure (see Figure 9 and S3 for experimental details). Extreme activation condi- tions were originally found to be necessary to overcome the strong binding between the DMF solvent and the open metal site and allow it to release through the narrow pore constrictions in the framework, 28 and we found that heating at 300 • C for 16 hours led to a structural change in the PXRD pattern of the activated sample. The primary reflection is preserved, suggesting that the unit cell remains unchanged.…”
Section: Experimental Activationmentioning
confidence: 71%
“…Second, rather than computationally screening hundreds of thousands of materials within the rigid structure approximation, we perform a set of detailed density functional theory (DFT) and grand canonical Monte Carlo (GCMC) calculations on a family of intrinsically flexible materials, known as M(NDC) (M={Ca,Sr}, NDC=1,4-naphthalenedicarboxylate). 28 DFT calculations validate some of the key geometric/energetic features of the flexible slit pore model that impart its high deliverable capacity.…”
Section: P [Bar]mentioning
confidence: 74%
“…2a and Scheme 2. The bond lengths of Cd(1)-N(4), Cd(1)-N(2), Cd(1)-N(3) and [16]. Finally compound II was strengthened by hydrogenbonding interactions (Table 3) and π−π stacking interactions with centroid-centroid distances ranging from 3.465(3) to 3.926(3) Å, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…3,4-Dicarboxyl-(3',4'-dicarboxylazophenyl)benzene (H 4 Dczpb) [15], 1,4-naphthalenedicarboxylic acid (H 2 Nda) [16,17], pyromellitic acid (H 4 Pma) [18,19] (Scheme 1) had been employed as exo-multidentate ligands for the design and construction of novel coordination polymers owing to their thermal stability and symmetry. In this paper, four supramolecular coordination compounds, namely [Cd(Phen) 2 6 ] · 2H 3 Pma · (H 2 Pma) · 2H 2 O (IV), constructed by Phen, and H 4 Dczpb, H 2 Nda, H 4 Pma with different transition metal ions (Cd 2+ , Mn 2+ , and Co 2+ ) were presented.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some Na + -based MOFs have also been reported to possess similar properties to their Li + analogs such as gas sorption, luminescence, and anodes for Na batteries. [22][23][24] Despite this, Na + -based MOFs have been less well studied, partly because the larger cation size results in increased coordination to polar solvents which favors low dimensional coordination networks. 9 Therefore, our understanding of the properties and applications of MOFs based on s-block metals lags significantly behind that of MOFs based on d-block metals.…”
Section: Introductionmentioning
confidence: 99%